Vertebral Column Metastases from an Esthesioneuroblastoma: Chemotherapy, Radiation, and Resection for Recurrence with 15-Year Followup. (19th February 2013) - Shirzadi, Ali S.; Drazin, Doniel G.; Strickland, Allison S.; Bannykh, Serguei I.; Johnson, J. Patrick
Abstract : Esthesioneuroblastoma (ENB) is an uncommon aggressive malignant intranasal neoplasm that originates from neural crest cells of the olfactory epithelium. Although local invasion to the sinuses is common, spinal metastasis of ENB is rare with only 28 documented cases involving the spine spinal cord, or leptomeninges. We report a case of ENB with multiple drop metastases to the cervical and thoracic spine, and review the patient's disease, medical history, and multiple interventions during a span of 15 years following the initial cranial resection. Despite aggressive multiple surgical resections, radiation, and chemotherapy, the tumor had significant progression and recurrence. The literature is reviewed, followed by a discussion of the natural progression of the disease and various reported interventions. Although a combination of surgery with chemotherapy and radiation therapy has been recommended, no definitive management has been established for ENB. Further research is needed to determine decisive treatment for metastatic ENB to the spine.